Ultrahigh Photoresponse of Few‐Layer TiS3 Nanoribbon Transistors. Issue 7 (8th April 2014) - Island, Joshua O.; Buscema, Michele; Barawi, Mariam; Clamagirand, José M.; Ares, José R.; Sánchez, Carlos; Ferrer, Isabel J.; Steele, Gary A.; van der Zant, Herre S. J.; Castellanos‐Gomez, Andres
<x xml:space="preserve">Abstract</x> TiS3 nanoribbons with thickness down to 15 nm are isolated by viscoelastic mechanical exfoliation. Field‐effect transistors are fabricated and their electrical characteristics are studied in the dark state and upon illumination. An ultrahigh photoresponse up to 3000 A/W, a bandgap of 1 eV, and response times of about 4 ms are found making TiS3 a state‐of‐the‐art material in photodetection. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>